2020
DOI: 10.1111/tpj.14855
|View full text |Cite
|
Sign up to set email alerts
|

A high activity zinc transporter OsZIP9 mediates zinc uptake in rice

Abstract: SUMMARY Zinc (Zn) is an essential micronutrient for most organisms including humans, and Zn deficiency is widespread in human populations, particularly in underdeveloped regions. Cereals such as rice (Oryza sativa) are the major dietary source of Zn for most people. However, the molecular mechanism underlying Zn uptake in rice is still not fully understood. Here, we report that a member of the ZIP (ZRT, IRT‐like protein) family, OsZIP9, contributes to Zn uptake in rice. It was expressed in the epidermal and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 61 publications
3
61
1
Order By: Relevance
“…Recently, it was reported that another ZIPmember, OsZIP9, contributes to Zn uptake in rice (Tan et al 2020, Yang et al 2020, Huang et al 2020b). OsZIP9 was localized at the exodermis and endodermis of mature root region and knockout of this gene resulted in significant decrease of Zn uptake under Zn‐limited condition (Huang et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that another ZIPmember, OsZIP9, contributes to Zn uptake in rice (Tan et al 2020, Yang et al 2020, Huang et al 2020b). OsZIP9 was localized at the exodermis and endodermis of mature root region and knockout of this gene resulted in significant decrease of Zn uptake under Zn‐limited condition (Huang et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Primary Zn uptake from the soil is likely performed by members of the ZIP (Zinc-regulated/Iron-regulated transporter Protein) family 8 10 . In rice, OsZIP9 was recently described as responsible for Zn acquisition from the rhizosphere 11 13 . The ZIP transporters were the first Fe and Zn transporters characterized in plants, and have been shown to transport Fe, Zn and other divalent cations in several plant species 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Primary Zn uptake are from the soil is likely 63 performed by genes of the ZIP (Zinc-regulated/Iron-regulated transporter Protein) family 64 (Assuncao et al, 2010;Milner et al, 2013;Sinclair et al, 2018). In rice, OsZIP9 was as 65 recently described as responsible for Zn acquisition from the rhizosphere (Huang et al, 66 2020;Tan et al, 2020;Yang et al, 2020). The ZIP transporters were the first Iron (Fe) and 67…”
mentioning
confidence: 99%